If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(n-1)+2=6n-8
We simplify the equation to the form, which is simple to understand
4(n-1)+2=6n-8
Reorder the terms in parentheses
+(+4n-4)+2=6n-8
Remove unnecessary parentheses
+4n-4+2=+6n-8
We move all terms containing n to the left and all other terms to the right.
+4n-6n=-8+4-2
We simplify left and right side of the equation.
-2n=-6
We divide both sides of the equation by -2 to get n.
n=3
| (3x-4)/5-7=0 | | 2(2y-1)=5(y+4) | | 2(2y-1)=5(4+4) | | (2x-3)/5=7 | | -1(w+0.2)=0.3(4-w) | | 5x^2+60x+25=0 | | x^2-17x-72=0 | | 5.5+4.1(7)-(7)= | | 10y-19-4y=12y-1 | | 2((2.7)+5(2.7))= | | 1/2(4.6)(8+6) | | 10x/2x | | a*a/a | | (a*a)/a | | 3(a+b)-3b= | | 3(a+b)-36= | | 4a*3= | | 5Q-40000=4Q-30000 | | x^2-y^2-4=0 | | 50p^2-162=0 | | p-2/15p | | x^2+8x+16=x^2+4x+4+84 | | 4x-3=17-x | | 11m+13=m+28 | | 1/5(2y-1)=1/2(y+4) | | 5e+7f=82 | | (3x-8)/12 | | 32y^2-24y=0 | | 4x^2-x-16= | | 3x^2-11x-1600=0 | | 4*-36= | | 9/64+6 |